diary of a wipy kid Jeff Kinney - Kinney, Jeff (London Puffin books, 2019)
Big changes are in store for Greg Heffley and his family. They are making home improvements! But with unwelcome critters, toxic mould and the walls coming down, soon Greg discovers renovations aren't all they are cracked up to be. When the dust finally settles, will the Heffleys be able to stay . . . or will they need to get out of town?
English Stories
Over 200 million books sold
For children from 11 to 15 years old
1 2
Keywords: Diary fiction; English stories